PENGARUH KUALITAS PELAYANAN, SERVICESCAPE DAN LOKASI TERHADAP KEPUTUSAN BEROBAT PASIEN RAWAT JALAN DI RUMAH SAKIT HARUM SISMA MEDIKA - Rianita Rahmadania; Jamaludin Khalid (LPPM Universitas Asa Indonesia, 2021)
This study aims to determine the effect of service quality, servicescape, and location on treatment decisions at Harum Sisma Medika Hospital. This research is a quantitative survey approach. Populations in this research are all outpatient of the Harum Sisma Medika Hospital with a sample of 100 respondents by accidental sampling. Data was collected by using a self-administered questionnaire method that has been tested its validity and reliability. The data analysis method used in this research is multiple linear regression analysis. The result of this study shows that service quality has a significant effect on treatment decisions at Harum Sisma Medika Hospital while showing that servicescape has no significant effect on treatment decisions at Harum Sisma Medika Hospital. It is also that location has not affected significantly on treatment decisions at Harum Sisma Medika Hospital. Finally, the result of simultan shows there is service quality, servicescape, and location on treatment decisions at Harum Sisma Medika Hospital have a significant effect with the percentage 37,7%